Credit as an instrument for growth: A monetary explanation of the Chinese growth story - Peter Bofinger; Lisa Geißendörfer; Thomas Haas; Fabian Mayer (University of Würzburg, Department of Economics, 2023)
This study describes the Chinese growth model over the past 40 years. We show that China's growth model, with its dominant role of the banking system and "the banker", is a perfect illustration of the necessity and power of Schumpeter's "monetary analysis". This approach has allowed us to elaborate theoretically and empirically the uniqueness of the Chinese model. In our empirical analysis, we use a new dataset of Chinese provincial data to analyze the impact of the financial system, especially banks, on Chinese economic development. We also empirically assess the role of the financial system in Chinese industrial policy and provide case studies of the effects of industrial policy in specific sectors. Finally, we also discuss macroeconomic dimensions of the Chinese growth process and lessons that can be drawn from the Chinese experience for other countries.
urn:nbn:de:bvb:20-opus-328804
Keywords: E; 330; Bank credit; Bank-led Growth; China; Economic development; Economic growth; Finance; Finance-growth nexus; Industrial Policy; Strategic Emerging Industries